ISOLASI DAN KARAKTERISASI JAMUR DARI PUPUK KOMPOS LIMBAH SAWIT - Sa’adah, Saroh Ziatun; Lestari, Widya; Harahap, Fitra Syawal; Yusida Saragih, Siti Hartati (Agros Journal of Agriculture Science, 2024)
Oil palm plants are commodities that play an important role in improving the national economy, especially increasing employment opportunities and increasing state income. This research aims to microscopically isolate fungi from palm oil waste compost. This research method is used descriptively using quantitative methods. Research has been carried out by taking samples of palm waste fertilizer, isolation, purification and microscopic observations. The fungal isolation medium used was Potato Dextrose Agar (PDA). Based on the results of fungal isolation from empty oil palm bunches (TKKS), 1 fungal isolate was obtained which had a round shape, had septa and had hyphae whose cells were separated by partitions called septa and were branched. The conodiophores are white, appear straight and branched, characteristic of the purple hyphae with white spots and white spores. Key words: empty palm oil bunches; isolation; fungi